Peningkatan Kesejahteraan Masyarakat di Desa-Desa Kecamatan Jatirogo, Kabupaten Tuban melalui Program Kotak Infaq Nahdlatul Ulama (Koin NU) - Muttaqin, Zainal; Arifah, Cinthiya Zakiah (Program Studi Ekonomi Syariah STAI Senori Tuban, 2024)
This research aims to determine the improvement in community welfare in the villages of Jatirogo District, Tuban Regency through the Nahdlatul Ulama Infaq Box (NU Coin) program. This research uses qualitative methods, which are used to describe conditions and also in the field in accordance with theory, using interviews, observation, and documentation. The results of this research show that the NU coin program was basically founded purely because of awareness of financial donations from the community in Jatirogo District. Collecting funds for NU Coins is usually done by distributing boxes of NU Coins to each branch in the Jatirogo District. The funds obtained are then collected and recorded directly by the chairman or secretary of UPZIS – LAZISNU Jatirogo. Later, these funds will be managed and used for NU activities, such as improving the welfare of the community in villages in Jatirogo District, starting to be used for social funds, then education, and finally for death assistance. As for obtaining funds, each branch usually receives around IDR 200,000 to IDR 1,500,000 per month. The funds collected are usually divided into 3 parts, namely 5% goes to the district, 20% goes to the sub-district, and 75% goes to the branches.